CENTRO MULTIDISCIPLINARIO EL MARACANA: Equipamiento Multidisciplinario Deportivo/recreativo Y Cultural (2023)
The city of Ibagué has a high public space deficit, since it has 1.2M2 per inhabitant when the World Health Organization (WHO) recommends that it be 15M2 per inhabitant, this was due to the accelerated and unplanned growth in the city over the years, we see this clearly in commune 12, since this commune was formed by families that arrived little by little to the sector, therefore this problem results in the lack of multipurpose and urban spaces that help with the city's public space, especially suitable sports equipment that complies with regulations.